Badanie potencjału możliwości uczenia się dzieci – eksperyment nauczający - Ewa Filipiak (Problemy Wczesnej Edukacji)
Vygotsky’s cultural-historical theory introduced new procedures in research methodology referring to the relationship between the zone of actual and proximal development. In the article I share my research experience resulting from an attempt to use in my research a teaching experiment in the understanding of Lev S. Vygotsky, the transition from the study of existing learning culture products and the diagnosis of the zone of actual development, the exploration of the child’s learning potential, his/her susceptibility to teaching, estimation of the child’s proximal development and cognitive readiness; from organizing a research situation in which the child independently solves the problem to exploring the potential of a child to solve a problem in cooperation with an adult, finally from examining both the child and the context to the study of the child in the context.